2020
DOI: 10.1088/1757-899x/993/1/012133
|View full text |Cite
|
Sign up to set email alerts
|

Fabrication and Characteristization of Bagasse Ash Particle (BAP) Reinforced Magnesium (AZ91E) Alloy Composite by Vacuum Stir Casting

Abstract: The present study is to fabricate AZ91E alloy matrix composite by varying the Bagasse ash particle (50μm) content (0, 5, 7.5, and 10wt%) via vacuum stir casting technique. The samples were characterized for its mechanical and microstructure properties. The mechanical properties of BAP reinforced composites were evaluated as per the ASTM standard and compared to unreinforced AZ91E alloy. The effect of reinforcement and distribution of BAP has been examined through a scanning electron microscope. The results of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 12 publications
0
2
0
Order By: Relevance
“…The externally preheated melon shell and fly ash particles with 50 μm coarse size feed into the furnace crucible maintained at the temperature of 550°C. A similar viscosity is retained during the complete mixing of aluminum alloy molten metal/melon shell ash/fly ash via 500 rpm continuous stir action help to increase the particle distribution results and attain good mechanical and tribological properties (Thirugnanasambandham & Chandradass, 2020; Rajan et al., 2007). The even mixed molten metal constitutions are transferred into the mold box and form the green metal casting size of 100 mm × 100 mm × 20 mm.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The externally preheated melon shell and fly ash particles with 50 μm coarse size feed into the furnace crucible maintained at the temperature of 550°C. A similar viscosity is retained during the complete mixing of aluminum alloy molten metal/melon shell ash/fly ash via 500 rpm continuous stir action help to increase the particle distribution results and attain good mechanical and tribological properties (Thirugnanasambandham & Chandradass, 2020; Rajan et al., 2007). The even mixed molten metal constitutions are transferred into the mold box and form the green metal casting size of 100 mm × 100 mm × 20 mm.…”
Section: Methodsmentioning
confidence: 99%
“…The sugar cane wastage of bagasse ash used as reinforcement for aluminum alloy found increased the mechanical and thermal performance of composite (Hassan & Aigbodion, 2010). The same way waste bagasse used magnesium alloy (AZ91E) composite was developed by vacuum stir casting route to enhanced hardness and strength of 83.33 Hv and 213.99 MPa, respectively (Thirugnanasambandham & Chandradass, 2020). The industrial waste fly ash prepared aluminum alloy composite observed high tensile strength in structural applications (Rajan et al., 2007).…”
Section: Introductionmentioning
confidence: 99%